Caries experience and salivary physicochemical characteristics among overweight intermediate school females aged 13-15 years in Babylon - Iraq - Aseel I Mohammed; Ban S Diab (College of Dentistry/ University of Baghdad, 2014)
Background: Obesity is a serious public health concern that has reached epidemic proportions; the prevalence, as well as the severity of obesity in adolescents is increasing at an alarming rate. A close relationship was found between weight status and dental caries. Thus this research aimed to assess the prevalence and severity of dental caries among overweight adolescent females in relation to physicochemical characteristics of stimulated whole saliva in comparison with normal weight adolescent females. Materials and methods: The total sample involved for nutritional status assessment is composed of 2678 females aged 13-15 years. This was performed using Body Mass Index specific for age and gender according to CDC growth chart (2000). The diagnosis and recording of dental caries was by using Decay, Missing, Filled surface index (DMFs); and according to the criteria of Manji et al (1989). Salivary samples were collected from 30 overweight females and their control under standardized conditions and then analyzed for measuring salivary flow rate and viscosity, in addition to estimation essential elements (zinc, copper, calcium, iron, and total protein). Results: The caries experience among the overweight females was lower than that among the normal weight with non significant difference. Salivary analysis demonstrated that the salivary flow rate was non significantly higher among overweight females. The viscosity of saliva was having an equal value among both groups. The data analysis of salivary elements found that the zinc and copper concentrations were highly significant higher among the overweight females than that among the normal weight. The opposite result found concerning salivary calcium level with also highly significant difference; while the iron and total protein were non significantly lower among the overweight females. DMFs and its grades correlated negatively weak with salivary flow rate among overweight females; while concerning salivary viscosity, the correlation was direct weak with DMFs. Salivary copper, calcium and total protein showed an inverse correlation with dental caries. Conclusion: The results of the current research revealed that overweight affect the caries experience. Several of salivary factors that found to be higher among the overweight females might play a role in protection of teeth from dental caries.